2021
DOI: 10.1177/0271678x211029884
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric cerebral blood flow predicts outcome in acute small subcortical infarcts

Abstract: The association between baseline perfusion measures and clinical outcomes in patients with acute small subcortical infarcts (SSIs) has not been studied in detail. Post-processed acute perfusion CT and follow-up diffusion-weighted imaging of 71 patients with SSIs were accurately co-registered. Relative perfusion values were calculated from the perfusion values of the infarct lesion divided by those of the mirrored contralateral area. The association between perfusion measures with clinical outcomes and the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Next, the final voxel-wise mean perfusion values representing the weighted average value of each ROI were calculated based on a previous method. 14 Normalized rCBF, rCBV, rMTT, and rTTP values were calculated as the ratio of ROI 1 to ROI 2.…”
Section: Methodsmentioning
confidence: 99%
“…Next, the final voxel-wise mean perfusion values representing the weighted average value of each ROI were calculated based on a previous method. 14 Normalized rCBF, rCBV, rMTT, and rTTP values were calculated as the ratio of ROI 1 to ROI 2.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, minor stroke was defined by an NIHSS score of 0–3, which was different from our study 24 . In addition to demographic profiles, the underlying reasons for this discrepancy in results might include thrombus characteristics, early recanalization, hemispheric cerebral blood flow, etc 25,26 . Besides, so far, the association between IV t‐PA and long‐term functional outcome in minor stroke patients was seldom reported.…”
Section: Discussionmentioning
confidence: 59%
“…A recent retrospective study showed mild neurologic deficits might mean less penumbra and lower hemispheric cerebral blood flow, and even given reperfusion, the benefit was limited, 25 which needed further validation. Also, in the NIHSS score of 0-2 subgroup, we observed the effect size of IV t-PA on functional outcome was enlarged from 3-, 6-month to 1-year follow-up, which was not obvious in the NIHSS score of 3-5 subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of AIS patients who underwent EVT with large vessel recanalization also had poor functional outcomes, of which impaired microvascular reperfusion played a major role 42 . Recent studies have shown that favorable collateral status predicted less cerebral edema, whereas the embarrassed microcirculation and collateral compensatory capacity were related to larger cerebral infarction, 43,44 which could affect the functional outcomes both in patients with small subcortical infarct or LVO 45,46 . Yang et al found that as an adjunct to EVT, IV tirofiban increased recanalization from 64.1% to 96.7% as compared with the control group, with an increased rate of 3‐month good outcome (41.4% vs. 12.2%) 47 .…”
Section: Discussionmentioning
confidence: 99%
“… 42 Recent studies have shown that favorable collateral status predicted less cerebral edema, whereas the embarrassed microcirculation and collateral compensatory capacity were related to larger cerebral infarction, 43 , 44 which could affect the functional outcomes both in patients with small subcortical infarct or LVO. 45 , 46 Yang et al found that as an adjunct to EVT, IV tirofiban increased recanalization from 64.1% to 96.7% as compared with the control group, with an increased rate of 3‐month good outcome (41.4% vs. 12.2%). 47 Thus, tirofiban which can facilitate the recanalization rate and reperfusion process is suitable for patients with incomplete recanalization and non‐recanalization after EVT.…”
Section: Discussionmentioning
confidence: 99%